Principles of computer security: CompTIA security+ and beyond (exam SY0-601) - Conklin, Arthur; White, Gregory; Cothren, Chuck; Davis, Roger L.; Williams, Dwayne (McGraw-Hill, 2022)
Embark on a transformative journey with our exhaustive CompTIA Security+ Training Guide, meticulously designed to pave your path from a cybersecurity enthusiast to a certified expert. This extensive course is your ultimate roadmap to mastering the wide-ranging concepts of information security, from the foundational cybersecurity frameworks to the advanced mechanisms of risk management. Each section unfolds progressively, allowing you to build upon your knowledge through engaging lessons that cover essential security roles, threat types, cryptographic solutions, and much more. As cyber threats grow more sophisticated, the demand for professionals equipped with comprehensive and advanced skills has skyrocketed. Our course not only delves into theoretical knowledge but also provides hands-on practical scenarios to solidify your understanding. With over 30 hours of expert content, you'll learn the intricacies of securing networks, managing vulnerabilities, and ensuring resilience in the face of digital threats. By the end of this course, you'll not just be prepared to ace the CompTIA Security+ exams but also to tackle real-world security challenges with confidence and expertise. What you will learn Summarize fundamental security concepts to build a strong base. Compare various threat types to better understand security breaches. Explain cryptographic solutions to secure organizational data. Implement robust identity and access management controls. Secure enterprise and cloud network architectures against potential threats. Enhance application security capabilities and ensure software integrity. Audience This course is tailored for IT professionals eager to climb the cybersecurity career ladder, entry-level individuals ready to step into the security arena, and students focused on carving out a future in information security. It's also the perfect starting point for anyone seeking to build a solid foundation in cybersecurity principles, offering the knowledge and credentials needed to thrive in this dynamic field. About the Author Alexander Oni : Alexander Oni is a bestselling instructor, with 70,000 students enrolled in his courses. His passion includes teaching through online courses in an entertaining way. Alex has been teaching online for more than five years and has created over 25 courses with numerous students registered worldwide. Alex believes we all have one shot at life and should live life to the fullest, constantly stepping out of our comfort zone, visiting places, and trying new things. His online success has given him financial freedom and the ability to travel and settle anywhere. The author is currently avidly traveling, spending a month in every city, and moving to the next. His hobbies include watching movies, sports, and chess.